KEUNGGULAN BERSAING BERBASIS DIGITAL MARKETING DAN INOVASI PRODUK PADA UMKM PRODUKTIF DI KOTA TANGERANG SELATAN (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine the effect of digital marketing and product innovation on competitive advantage in productive MSMEs in South Tangerang City, either partially or simultaneously. The method used is quantitative. The sampling technique used was saturated sampling and the sample obtained in this study amounted to 130 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are digital marketing has a significant effect on competitive advantage with the regression equation Y = 15.757 + 0.608X1, the correlation value is 0.682 means that the two variables have a strong relationship level. The value of the coefficient of determination is 46.5%. Hypothesis test obtained t arithmetic > t table or (9.139% > 0.985%). Thus H0 is rejected and H1 is accepted, meaning that there is a significant influence of digital marketing on competitive advantage. Product innovation has a significant effect on competitive advantage with the regression equation Y = 14,284 + 0.642X2, the correlation value of 0.661 means that the two variables have a strong relationship level. The value of the coefficient of determination is 43.7%. Hypothesis test obtained t count > t table or (8.633% > 1.985%). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of product innovation on competitive advantage. Digital Marketing and Product Innovation have a significant effect on competitive advantage with the regression equation Y = 10,585 + 0.385X1 + 0.356X2. The correlation value of 0.733 means that the independent variable and the dependent variable have a strong level of relationship. The value of the coefficient of determination is 53.7% while the remaining 46.3% is influenced by other factors. Hypothesis test obtained value of F count > F table or (55,196 > 3.09). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence of digital marketing and product innovation on the competitive advantage of Productive MSMEs in South Tangerang City.